2020
DOI: 10.1002/brb3.1652
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of local functional connectivity in lifespan: A resting‐state fMRI study

Abstract: Introduction As aging attracted attention globally, revealing changes in brain function across the lifespan was largely concerned. In this study, we aimed to reveal the changes of functional networks of the brain (via local functional connectivity, local FC) in lifespan and explore the mechanism underlying them. Materials and Methods A total of 523 healthy participants (258 males and 265 females) aged 18–88 years from part of the Cambridge Center for Ageing and Neurosci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 53 publications
6
16
1
1
Order By: Relevance
“…Therefore, understanding the age-related changes in resting-state functional connectivity (rsFC) is crucial to decipher the impact of bilingualism. Alerting, orienting, and executive control are often related to the various predefined resting-state intrinsic networksfrontoparietal attention network (FPAN), dorsal and ventral attention network (DAN, VAN) (Fan et Studies have shown an age-related decline in functional connectivity within the default mode network (DMN; Wen, He, Dong, Chen, Yang, Guo, Luo, & Yao 2020), FPAN (Yao, Yang, Hwang & Hsieh., 2020), and visual network (VN; Wen et al, 2020). In contrast, some studies suggest an increase in functional connectivity with age for the frontal and parietal network (involved in attention), also in somatosensory, motor cortices, and subcortical networks (Damoiseaux, 2017;Ferreira & Busatto, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, understanding the age-related changes in resting-state functional connectivity (rsFC) is crucial to decipher the impact of bilingualism. Alerting, orienting, and executive control are often related to the various predefined resting-state intrinsic networksfrontoparietal attention network (FPAN), dorsal and ventral attention network (DAN, VAN) (Fan et Studies have shown an age-related decline in functional connectivity within the default mode network (DMN; Wen, He, Dong, Chen, Yang, Guo, Luo, & Yao 2020), FPAN (Yao, Yang, Hwang & Hsieh., 2020), and visual network (VN; Wen et al, 2020). In contrast, some studies suggest an increase in functional connectivity with age for the frontal and parietal network (involved in attention), also in somatosensory, motor cortices, and subcortical networks (Damoiseaux, 2017;Ferreira & Busatto, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Functional connectivity between brain regions can change rapidly over time ( Hutchison et al, 2013 ; Robinson, Atlas, & Wager, 2015 ), is not easily predictable from anatomical connectivity ( Vanduffel, Payne, Lomber, & Orban, 1997 ), and is altered in several different pathological states ( Damaraju et al, 2014 ; Damoiseaux, Prater, Miller, & Greicius, 2012 ; Schmidt, Carpenter-Thompson, & Husain, 2017 ; Supekar, Menon, Rubin, Musen, & Greicius, 2008 ). In addition, cortical networks appear particularly vulnerable to aging and demonstrate diminished network-level functional connectivity over the lifespan ( Andrews-Hanna et al, 2007 ; Ash et al, 2016 ; Battaglia et al, 2020 ; Tomasi & Volkow, 2012 ; Wen et al, 2020 ). Furthermore, aging-related disruptions in functional connectivity correlate with declines in cognitive performance ( Onoda, Ishihara, & Yamaguchi, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, seeds in the alerting network (right superior temporal gyrus and left inferior parietal lobe) show a negative correlation with various occipital regionsleft inferior lateral occipital cortex and right lingual gyrus, and occipital pole. Various rsFC studies in the past have reported an overall negative network correlation between a visual network with frontoparietal, dorsal, and ventral attentional networks (Wen et al, 2020). In addition to the network dynamics, the negative association between L2 task proficiency and rsFC can be explained by the age-related shift on the impact of cognitive reserve variables.…”
Section: L2 Proficiency and Exposuresubjective Measurementioning
confidence: 96%
“…Thus, attention is, inarguably, a gateway to working memory (Awh, & Jonides, 2001; Mackie, Van Dam, & Fan., 2013) and is vital to implement cognitive control (Mackie et al, 2013). Several studies tapping into the subcomponents of attention have shown better performance for the bilinguals (Costa et al, 2008 Wen et al, 2020). In contrast, some studies suggest an increase in functional connectivity with age for the frontal and parietal network (involved in attention), also in somatosensory, motor cortices, and subcortical networks (Damoiseaux, 2017;Ferreira & Busatto, 2013).…”
Section: Introductionmentioning
confidence: 99%